The relationship between hotel attributes of online reviews and young adult travellers' purchasing decisions towards budget hotels: a case study of TripAdvisor / Nur Hanun Muhammad - Muhammad, Nur Hanun (2022)
Online reviews on the travel website or similar digital platforms play a significant role as a reliable source of information for travellers before they purchase the booking at a budget hotel room. Many travellers including young adults can be influenced by the online reviews through the opinions and comments from other travellers about the hotel. Throughout the opinions and comments, young adult travellers might consider important factors before making a purchasing decision. In the literature, the important factors that influenced the purchasing decision were discussed by using the significant hotel attributes of online reviews. The hotel attributes were independent variables, namely price, location, cleanliness, room facilities and service; and customers' purchasing decisions as the dependent variable. The study hopes to reduce uncertainty and help young adult travellers to make decisions efficiently between many hotel attributes after going through 5 stages of the decision-making process consisting of 1) problem recognition, 2) information search, 3) evaluation of alternatives, 4) purchase decision, 5) post-purchase behaviour. The sample consisted of 386 respondents in the Klang Valley city area selected using the snowball sampling method. Data were obtained by distributing the structured questionnaires to working young adults who had experience using TripAdvisor. Data analysis was carried out using IBM Statistical Packaging for Social Science version 23.0 to answer research objectives and research questions. The result showed price was identified as the most influential hotel attribute among young adult travellers regardless of their stay purpose either leisure or business.